Solar Power Generation System with Low Temperature Heat Storage. (2016) - Dragomir-Stanciu, Daniel; Luca, Constantin
Abstract: The paper analyze a small power generating system that convert solar energy into electricity using an organic Rankine cycle. Solar thermal energy is stored at low temperature in a phase change material. The phase change material used is paraffin wax and the organic fluid is R134a. Was calculate the thermodynamic cycle and were established relationships to calculate the working agent mass flow and the necessary mass of phase change material, depending on the electric power produced.